Experimental and Numerical Modelling of Shear Behaviour of Full-scale RC Slabs Under Concentrated Loads. (May 2017) - Nana, W.S.A.; Bui, T.T.; Limam, A.; Abouri, S.
Abstract: In nuclear buildings, situations such as localized heavy loads from equipment, slabs loaded by walls or columns are commonly found. For constructability and cost-effectiveness reasons, shear reinforcement of concrete is an important issue in a new nuclear plant project. This study presents an experimental and numerical investigation of the shear behaviour of full-scale reinforced concrete (RC) slabs without shear reinforcement under a concentrated load near a linear support in nuclear buildings. The main aim was to evaluate experimentally and numerically the influence of several variables: bottom longitudinal reinforcement, bottom transverse reinforcement, compressive strength, concrete aggregate size, slab depth and loading plate length on the shear behaviour of RC slabs under a concentrated load. First, an experimental campaign was performed: a series of ten tests on nine full-scale slabs (one slab measuring 3.2 m × 2.9 m × 0.3 m; six slabs measuring 4 m × 2.6 m × 0.3 m; one slab 4 m × 2.6 m × 0.35 m and one slab 4 m × 2.6 m × 0.4 m) already presented in Bui et al. (2016). The originality of this study is that three new tests added three full-scale slabs measuring 4 m × 2.6 m × 0.3 m to analyse the influence of the compressive strength and the loading plate length on the slabs' shear strength, which had not been tested in the 2016 study. Then concrete damaged plasticity (CDP) in Abaqus software was used for three-dimensional (3D) modelling and calibration. The proposed numerical model showed that the RC slabs' behaviour was in good agreement with the experimental results.